Penerapan Green Budgeting: Strategi Pemerintah Daerah untuk Pembangunan Berkelanjutan - S, Suharyono (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Environmental sustainability issues are increasingly becoming a major concern in regional fiscal policy. This study aims to analyze the implementation of green budgeting in the 2025 Bengkalis Regency Regional Budget (APBD), focusing on the extent to which regional programs and activities support the principles of environmental sustainability. The study uses a qualitative approach with a descriptive-analytical type, through documentation studies, interviews, and observations. The analysis was conducted using the green tagging method to classify regional spending into three categories: green, gray, and red. The results show that of the total APBD of Rp 3,217,264,617,959, only around Rp 122 billion (3.79%) can be classified in terms of its impact on the environment. The green budget allocation of Rp 12.5 billion (0.73%) covers mangrove conservation programs, community-based waste management, pollution control, and environmental education. Meanwhile, the neutral budget of Rp 24.5 billion (1.44%) and the red budget of Rp 85 billion (2.64%) reflect activities that have the potential to cause negative impacts on the environment if not accompanied by mitigation. These findings indicate that despite initial awareness of environmental issues, the implementation of green budgeting in Bengkalis Regency is still in its early stages and requires strengthening of regulations and institutions, as well as increasing the proportion of green budgets in the future.